2013
DOI: 10.31729/jnma.571
|View full text |Cite
|
Sign up to set email alerts
|

I-gel for Positive Pressure Ventilation

Abstract: Introduction: I-gel is a relatively new supra-glotitc airway device which is claimed to be superior to laryngeal mask airway. It can be used ingeneral anesthesia with spontaneous ventilation as well as with positive pressure ventilation.This study was designed to assess whether I-gel creates adequate laryngeal seal during positive pressure ventilation in patients undergoing laparoscopic surgery. Methods: A prospective randomized study was made among the 60 patients who underwent laparoscopic cholecystect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…[18,21,22,31,32] The combined results showed no evidence of any difference between the groups (RR 3.65, 95% CI 1.39–9.62, P chi 2 = 0.996, I 2 = 0.0%, NNT = 24).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…[18,21,22,31,32] The combined results showed no evidence of any difference between the groups (RR 3.65, 95% CI 1.39–9.62, P chi 2 = 0.996, I 2 = 0.0%, NNT = 24).…”
Section: Resultsmentioning
confidence: 98%
“…[2327,31,32] Pooled analysis showed that the incidence of laryngospasm was higher in the ETT group than in the SGA group (RR 3.12, 95% CI 1.29–7.52, P chi 2 = 0.995, I 2 = 0%, NNT = 21) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The sealing pressure serves as an index of airway and respiratory mechanics (33) . Hence high oropharyngeal leak pressures are necessary to deliver the required increased peak airway pressures without the fear of leak, gastric insufflation and resultant pulmonary aspiration.…”
Section: Discussionmentioning
confidence: 99%